Assessment of mental distress among prison inmates in Ghana's correctional system: A cross-sectional study using the Kessler Psychological Distress Scale - Ibrahim, A.; Esena, R.K.; Aikins, M.; O'Keefe, A.M.; McKay, M.M. (International Journal of Mental Health Systems, 2015)
Applying global estimates of the prevalence of mental disorders suggests that about 2.4 million Ghanaians have some form of psychiatric distress. Despite the facts that relatively little community-based treatment is available (only 18 psychiatrists are known to actively practice in Ghana), and that mental disorders are more concentrated among the incarcerated, there is no known research on mental disorders in Ghana prisons, and no forensic mental health services available to those who suffer from them. This study sought to determine the rate of mental distress among prisoners in Ghana. Methods: This cross-sectional research used the Kessler Psychological Distress Scale to estimate the rates and severity of non-specific psychological distress among a stratified probability sample of 89 male and 11 female prisoners in one of the oldest correctional facilities in the country. Fisher's exact test was used to determine the rates of psychological distress within the study population. Results: According to the Kessler Scale, more than half of all respondents had moderate to severe mental distress in the four weeks preceding their interviews. Nearly 70% of inmates with only a primary education had moderate to severe mental distress. Though this was higher than the rates among inmates with more education, it exceeded the rates for those with no education. Conclusions: The high rate of moderate to severe mental distress among the inmates in this exploratory study should serve as baseline for further studies into mental disorders among the incarcerated persons in Ghana. Future research should use larger samples, include more prison facilities, and incorporate tools that can identify specific mental disorders. © Ibrahim et al.; licensee BioMed Central.
Keywords: Ghana prisons; Kessler Psychological Distress Scale; Mental health; Northern Ghana